2011
DOI: 10.1103/physrevb.84.174429
|View full text |Cite
|
Sign up to set email alerts
|

Competing interactions and magnetic frustration in Yb4LiGe4

Abstract: We have studied polycrystalline Yb 4 LiGe 4 , a ternary variant of the R 5 T 4 family of layered compounds characterized by a very strong coupling between the magnetic and crystallographic degrees of freedom. The system is mixed valent, with non-magnetic Yb 2+ and magnetic Yb 3+ present, and is characterized by coexisting ferromagnetic and antiferromagnetic correlations. We present measurements of resistivity, AC-susceptibility, specific heat, and muon spin relaxation (μSR), below 1 K. The low temperature meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Several systems combining rare earth elements with germanium and lithium have been studied 9. Other than in our recent work on Yb 4 LiGe 4 , the physical properties of these compounds have not been studied in detail 9,10. The low heats of vaporization of europium and ytterbium11 limit the synthesis of their compounds compared to other phases based on rare earth metals.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Several systems combining rare earth elements with germanium and lithium have been studied 9. Other than in our recent work on Yb 4 LiGe 4 , the physical properties of these compounds have not been studied in detail 9,10. The low heats of vaporization of europium and ytterbium11 limit the synthesis of their compounds compared to other phases based on rare earth metals.…”
Section: Introductionmentioning
confidence: 95%
“…[5,6] Eu 2 LiGe 3 crystallizes in an orthorhombic Ca 2 LiSi 3 -type structure, and its detailed crystal structure and electronic characterization were studied by Xie et al [6] They also observed EuLiGe 2 as a side product during their synthesis of Eu 2 LiGe 3 . [8][9][10] Several systems combining rare earth elements with germanium and lithium have been studied. The single-crystal structure of YbLiGe 2 was studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three degenerate configurations for the ground state where we can arrange the spins so that two bonds are AFM and one bond is FM ( Fig. 2 as in Villain model [36], in R 5 T 4 (R = rare earth, T = Ge or Si) [37] where the FM intra-layer interaction competes with the AFM inter-layer interaction, in J 1 − J 2 square lattice where FM NN (along the side) and AFM next-nearest-neighbor (NNN) interactions are comparable (to be discussed later in this chapter), in double pervoskite (A 2 BB O 6 , A = Ca, Ba, Sr, B, B = transition metals) family of compounds [38] where inequivalent NN and NNN exchange interactions compete, in spinels AB 2 O 4 where frustration arises since within each sublattice there is AFM coupling (to be discussed later in this chapter), and in spin ladder compounds [39] where frustrated interchain exchange interactions occur both on rungs and diagonals. Since frustration results in multi-degenerate ground states rather than one unique stable one, introduction of very small perturbations or fluctuations in the system cause very novel and exotic phenomena to emerge many of which have not been well explained or understood yet.…”
Section: Frustrationmentioning
confidence: 99%